Sporadic rainy events are more critical than increasing of drought intensity for woody species recruitment in a Mediterranean community. - Matías, Luis; Zamora, Regino; Castro, Jorge (Oecologia, 2012)
The understanding of the impact of extreme climatic events under a global climate change scenario is crucial for the accurate forecast of future plant community dynamics. We have experimentally assessed the effect of drier and wetter summer conditions on the recruitment probabilities and the growth of seedlings from eight woody species representative of the most important functional groups in the community, pioneer shrubs, mid-successional shrubs and trees, across the main habitats in the study area (open habitat, shrubland, and forest). Our hypothesis proposes that wet summer conditions would represent a good opportunity for tree species regeneration, enhancing both forest maintenance and expansion. A drier summer scenario, on the other hand, would limit forest regeneration, and probably hinder the colonization of nearby habitats. We found a habitat effect on the emergence, survival, and final biomass, whereas different climate scenarios affected seedling survival and biomass. A wet summer boosted growth and survival, whereas greater drought reduced survival only in some cases. These results were modulated by the habitat type. Overall, shrub species presented higher survival and growth and were less affected by more severe drought, whereas some tree species proved to be extremely dependent on wet summer conditions. We conclude that the reduction in frequency of wet summers predicted for the coming decades in Mediterranean areas will have greater consequences for species recruitment than will increased drought. The different response of the species from the various functional groups has the potential to alter the composition and dominance of future plant communities.
Keywords: Angiosperms; Angiosperms: growth & development; climate change; Droughts; Ecosystem; Mediterranean Region; Rain; rainfall variability; Recruitment; Seedling; Seedling: growth & development; Spain; summer drought; Vegetation dynamics

Evolution of annual rainfall irregularity in the southwest of the Iberian Peninsula - García-Barrón, L.; Aguilar, M.; Sousa, a (Theoretical and Applied Climatology, 2010)
The areas of the Iberian Peninsula with Mediterranean climate are characterised by rainfall irregularity. Standard statistical estimation methods provide a limited insight of all the dimensions of such irregularity. Based on different techniques to describe the inter-annual irregularity of rainfall, the authors develop a new method: the disparity indices. These indices are then applied to several historical rainfall series (dating from the end of the nineteenth century up to the present) from the southwest of the Iberian Peninsula. Similar rainfall irregularity patterns are found in all weather stations in the studied area, confirming their belonging to the same climatic region. The results indicate a relative stability during the first third of the twentieth century, coinciding with a period of low precipitation and a progressive increase during the last three decades. The use of a new index named specific disparity index has proven be useful in highlighting the irregularity within the rainfall series at each meteorological station. This new index could contribute to monitor future changes in precipitation within the general framework of research on climate change. Although Mediterranean ecosystems are adapted to important fluctuations in the rainfall regime, this increase in irregularity may affect rivers, wetlands and the hygrophytic vegetation.
Keywords: climatic series; disparity index; Iberian Peninsula (voyant); rainfall variability

Analysis of rainfall trends and dry periods on a pluviometric gradient representative of Mediterranean climate in the Duero Basin, Spain - Ceballos, Antonio; Martı́nez-Fernández, José; Luengo-Ugidos, Miguel Ángel (Journal of Arid Environments, 2004)
The present work studies the trends in rainfall and the behaviour of dry spells along a pluviometric gradient representative of the conditions of the Mediterranean region. The region is characterized by a marked water deﬁcit in the summer, a pronounced irregularity in its rainfall regime, and a noteworthy frequency of dry spells or periods without appreciable rainfall. The results obtained conﬁrm the general previsions of the IPCC, with a predominance of dry years over wet ones and a negative rainfall trend in the central sector. An increase in intra-annual variability in rainfall, and a very pronounced occurrence of dry periods independent of the total annual rainfall, are also seen. These circumstances will potentially increase the vulnerability of several Mediterranean ecosystems located along the gradient that are currently subject to considerable pressure from human activities; this will increase the environmental problems of these zones (agro-forestry–grazing productivity, soil degradation, recharge of aquifers, forest ﬁres, runoff models, biological diversity and composition, etc.).
Keywords: dry spells; duero basin; Mediterranean ecosystems; rainfall gradient; rainfall variability

Analysis of rainfall trends and dry periods on a pluviometric gradient representative of Mediterranean climate in the Duero Basin, Spain - Ceballos, Antonio; Martı́nez-Fernández, José; Luengo-Ugidos, Miguel Ángel (Journal of Arid Environments, 2004)
The present work studies the trends in rainfall and the behaviour of dry spells along a pluviometric gradient representative of the conditions of the Mediterranean region. The region is characterized by a marked water deﬁcit in the summer, a pronounced irregularity in its rainfall regime, and a noteworthy frequency of dry spells or periods without appreciable rainfall. The results obtained conﬁrm the general previsions of the IPCC, with a predominance of dry years over wet ones and a negative rainfall trend in the central sector. An increase in intra-annual variability in rainfall, and a very pronounced occurrence of dry periods independent of the total annual rainfall, are also seen. These circumstances will potentially increase the vulnerability of several Mediterranean ecosystems located along the gradient that are currently subject to considerable pressure from human activities; this will increase the environmental problems of these zones (agro-forestry–grazing productivity, soil degradation, recharge of aquifers, forest ﬁres, runoff models, biological diversity and composition, etc.).
Keywords: dry spells; duero basin; Mediterranean ecosystems; rainfall gradient; rainfall variability